1997
DOI: 10.1021/es960292x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermal Effects on the Dissolution of a Nonaqueous Phase Liquid in Porous Media

Abstract: Porous media contaminated with nonaqueous phase liquids (NAPLs) may serve as a long-term source of groundwater contamination. To remove NAPLs and thereby mitigate the potential impact to the environment and human health, it has been suggested that contaminated media be flushed with cosolvents, surfactants, hot water, or steam. In this study, hot water flooding was used to remediate a porous medium contaminated with tetrachlorethylene (PCE) at residual saturation in an otherwise water-saturated medium. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 50 publications
2
39
2
1
Order By: Relevance
“…However, some authors report the effects of temperatures on the two-phase porous flow behavior. 5,[27][28][29][30][31][32][33][34][35][36][37][38][39][40] Sinnokrot et al 27 determined the effects of temperature on capillary pressure curves through measurement of drainage and imbibition capillary pressures for three consolidated sandstones and one limestone core. Lo and Mungan 41 proposed that oil recovery operations are more efficient at higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors report the effects of temperatures on the two-phase porous flow behavior. 5,[27][28][29][30][31][32][33][34][35][36][37][38][39][40] Sinnokrot et al 27 determined the effects of temperature on capillary pressure curves through measurement of drainage and imbibition capillary pressures for three consolidated sandstones and one limestone core. Lo and Mungan 41 proposed that oil recovery operations are more efficient at higher temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Typical thermal treatment applications increase temperatures to near the boiling point and mobilize DNAPL through generation of vapors which are extracted and treated. Imhoff et al, 1997 empirically and predicatively demonstrated that moderate temperature applications of hot water flushing for chlorinated solvent treatment enhance the mass transfer rate of residual DNAPL by a factor of four to five when temperatures were increased from 5 degrees Celsius ( o C) to 60 o C. Combining subsurface heating to moderate temperatures with in situ technologies, such as such as ZVI could negate the requirement for vapor extraction and treatment, which is a large fraction of the cost of typical thermal applications that reach boiling temperatures. For this approach to be viable, however, increases in physical mass transfer rates for both dissolution and volatilization as temperature increases must be balanced by reaction or contaminants will migrate out of the heated treatment zone without being degraded.…”
Section: Zvi Technologymentioning
confidence: 99%
“…31 Alguns estudos indicam que o uso de água quente pode ser uma técnica de remediação atraente quando a solubilização do contaminante é significantemente alterada com a temperatura ou se há limitações no bombeamento de fases não aquosas por causa de sua viscosidade. 32 De acordo com os resultados obtidos, esta técnica poderia ser aplicada no caso da solubilização das LNAPLs testadas.…”
Section: Influência Do Corante E Da Fase Orgânica Sobre O Desempenho unclassified